New easternmost and southernmost records of Pseudoboa coronata Schneider, 1801 (Serpentes: Dipsadidae: Pseudoboini), with a distribution map - Henrique Costa; Giselle Cotta; Ross MacCulloch (Check List, 2015)
The snake species Pseudoboa coronata has wide distribution from central Brazil to coastal Venezuela and the Guianas, eastern Bolivia, Colombia, Ecuador, and Peru. In this note, the known distribution range of P. coronata is extended eastward to the border between the states of Bahia and Pernambuco, and southward to Cachoeira Alta, state of Goiás, both in Brazil. Considering the limited biogeographic information for most taxa, reports like this add significant data for future studies on biogeography, taxonomy, and conservation biology.